Pengaruh Kepemimpinan Dan Lingkuan Kerja Terhadap Kinerja Melalui Motivasi Pada Pegawai Puskesmas Banjarejo Kabupaten Blora - Indriani, Etty; Sulistyowati, Nanik (-)
The aim of this research are to test the influences of the leadership and the job environment, the motivation (as intervening variable) toward the performance of officers at Puskesmas Banjarejo Kabupaten Blora.Keywords: the leadership, job environment, the motivation and the performance of officers